Neo-Ottomanism" in the Regional Policy of Turkey - Elnur Tadzhaddinovich Mehdiyev (Vestnik MGIMO-Universiteta, 2016)
The article is devoted to the ideology of Turkey's foreign policy. The term "neo-Ottomanism" is increasingly used in recent years in relation to the Turkish foreign policy. The concept of neo-Ottomanism, which ideology is the Prime Minister Davutoglu, implies a relationship of foreign policy of modern Turkey with the historical heritage of the Ottomans and its focus on return "last Ottoman", taking into account today's realities. The author examines this phenomenon in the context of the regional policy of Turkey in this period. The main directions of the strategy of neo are the Middle East, North Africa, Central Asia, the Caucasus, the Crimea, and the Balkans. Particular attention is paid to manifestations of neo-Ottomanism in the post-Soviet region and the Middle East, as well as "soft power" strategy in the Turkish neo-Ottomanism. Activities of Ankara in the regions belonging to the sphere of its geopolitical interests is carried out on political, economic, religious, cultural and educational levels. Rapprochement with the political and business circles of influence of countries in the region is aimed at the formation of pro-Turkish lobby. "Arab Spring" has given Turkey a historic opportunity to realize its neo-Ottoman ambitions and create a new order in the Middle East. Turkey's rapprochement with the Islamic world during the 'Arab Spring' demonstrated that Ankara supported in conjunction with the Western nations protest and opposition movements in Egypt, Libya and Tunisia, aims to demonstrate to the West the growth of its influence in the region. Mediation is used in regional conflicts Turkish leadership as an instrument of "soft power", with which Ankara aims to increase its international and regional credibility. The result of "neo-Ottoman" Turkey's policy in relations with Russia became a serious crisis in all spheres of cooperation. Strategic mistakes made by the head of the republic R. Erdogan in the settlement of the Syrian crisis, may lead to instability of the entire region. The author considers the possible directions of neo-Ottoman Turkey's policy in the studied regions in the near future.